Significant association of thrombocytopenia with chronic active hepatitis B virus infection in a tertiary care hospital of an intermediate prevalence HBV country (Asian Journal of Medical and Biological Research, 2019)
Thrombocytopenia is a relatively uncommon extra-hepatic manifestation of uncomplicated chronic hepatitis B virus (HBV) infection. This study has two aims: to assess the prevalence of thrombocytopenia in non-cirrhotic patients with chronic hepatitis B (CHB); and to determine the association of certain variables with thrombocytopenia in Duhok province. It is a case control study conducted in Azadi Teaching Hospital during June 2016 - May 2019. Chronic active hepatitis B was defined according to the following parameters: the presence of detectable hepatitis B surface antigen (HBsAg) in the blood longer than six months, positive or negative HBeAg, HBV-DNA level >2000 IU/ml, elevated ALT, and/or at least moderate histopathological fibrosis. Thrombocytopenia was defined as platelet counts below 150,000/μl. The obtained results were analyzed by entering data into Microsoft Excel 2010. A total of 379 CHB patients and 200 cases as control were enrolled in this study. Their mean ages were 33.62 ± 14.48 and 40.72 ± 18.56 for HBV and control cases, respectively. There were 236 (62.27%) males in the HBV patients and 109 (54.50%) males in the control group. Comparing both groups, significant association was found between HBV and younger age, cigarette smoking, and alcohol consumption. Chronic active hepatitis B without liver cirrhosis was strongly associated with an increased rate of thrombocytopenia. This finding is paramount as it is statistically significant (P = 0.042). Significant association with younger age and Syrian nationality was found more in CHB patients with thrombocytopenia compared to non-thrombocytopenic. In conclusion, chronic active hepatitis B is strongly associated with thrombocytopenia. As hypersplenism resulting from liver cirrhosis was excluded in our patients, the cause of thrombocytopenia is due to other mechanisms. Therefore, it is important to consider CHB in the differential diagnosis of patients presenting with isolated thrombocytopenia. Older age and Syrian nationality were predictors for developing thrombocytopenia in chronic active HBV infection.Asian J. Med. Biol. Res. June 2019, 5(3): 207-211